The Role of Tibialis Posterior Tendon Transfer in Correction of Foot Drop Deformity - Al- Iedani, Mohammed S.; Aaqail, Falah M; Majeed, Ghadeer H (AL-Kindy College Medical Journal, 2013)
Bac kground: The transfer of the tibialis posterior tendon to the anterior aspect of the ankle not only replaces the function of the paralyzed muscles, but also removes the deforming force on the medial aspect of the foot. Objec t i ves : In this study, we evaluated patients who underwent tibialis posterior tendon transfer for the treatment of foot drop, and comparison through interosseous membrane route versus anterior to lower tibia route of tibialis posterior tendon transfer, with evaluation of the results according to carayon criteria Methods: Nine patients with foot drop secondary to different causes treated with tibialis posterior tendon transfer from January 2011 to January 2012 were followed up for a mean of 12 months in Al Kindy Teaching Hospital. We use two different techniques, first transfer the tendon through the interosseous membrane (four patients), and the second technique transfer the tendon anterior to tibia (five patients). Resul t s : In general according to carayon evaluation criteria, the results were excellent in two patients (22.2%), good in five patients (55.6%), and moderate in two patients (22.2%). Through anterior to lower tibia route, 4 patients get excellent to good result (80%), and through interosseous route, 3patients get good to excellent result (75%). Conc lus ions : Transfer of tibialis posterior tendon for the treatment of foot drop deformity enables the patients to walk without the aid of orthosis and increase their quality of life. With no differences between anterior to lower tibia route and through interosseous membrane route.